THE INTERNATIONAL SMART WATER ACCOUNTING FOR SUSTAINABLE WATER SELF-SUFFICIENCY - Mohammad Sigit Adi Nugraha; Denny Aditya Dwiwarman; Wenny Djuarni; Ira Mariyah Ulfah (Amal Insani Foundation, 2026)
Water scarcity and inefficient water governance remain critical challenges for agricultural communities worldwide. This study aims to develop and analyze an International Smart Water Accounting framework to support sustainable water self-sufficiency through academic collaboration and community empowerment. The approach integrates water accounting principles, digital monitoring systems, and participatory governance to improve transparency, accountability, and efficiency in water resource management. Using a qualitative-descriptive and case-based approach, this study highlights how smart water accounting can be implemented as a scalable and replicable model across different agricultural contexts. The findings indicate that international academic collaboration enhances knowledge transfer, strengthens local capacity, and supports sustainable water governance aligned with global sustainability agendas. This study contributes to the advancement of water accounting practices and provides practical implications for policymakers, higher education institutions, and community-based water management initiatives